The Effect of Aging on Composition and Surface of Translucent Zirconia Ceramic - Korina Mešić; Igor Majnarić; Jasmina Obhodaš; Gorana Baršić; Ketij Mehulić (University of Zagreb. School of Dental Medicine, 2020)
Objectives: To examine the effect of two aging protocols on the chemical and phase composition as well as the surface state of monolithic translucent zirconia ceramics. Material and Methods: Trans-lucent zirconia ceramics KATANA-Zirconia STML with different surface treatments (no treatment, K1, K2; glazed, G1-G8; polished, P1-P8) underwent testing in order to examine how the two aging protocols (three-hour hydrothermal degradation in an autoclave at 134 °C and 2 bars: G1-G4, P1-P4, and sixteen-hour chemical degradation in four-percent acetic acid at 80 °C (ISO 6872): G5-G8, P5-P8) affect chemical composition, particularly the share of stabilizing yttrium oxide (Energy Dispersive X-Ray Fluorescence - EDXRF), phase composition (X-ray diffraction - XRD) and surface state in terms of roughness and gloss. Results: Aging protocols did not affect the tested chemical composition stability of specimens and a high share of stabilizing yttrium-oxide (≥10% of total content), which correlates with the absence of monoclinic phase. A decrease in gloss on all specimens is statistically significant. Chemical degradation substantially increased the surface roughness of tested specimens. Conclusions: Translucent monolithic zirconia demonstrated a stable chemical composition and resistance to tetragonal-to-monoclinic transformation. Surface gloss was significantly reduced, especially in polished specimens. Contrary to glazed specimens, the tested polished specimens manifested an increase in surface roughness. Glazing the surface of translucent monolithic zirconia produces better esthetic, tribological and hygienic effects than polishing.